Verbascum ibrahim-belenlii (Scrophulariaceae), a new species from East Anatolia, Turkey - Karavelioğulları, Faik Ahmet (Phytotaxa, 2015)
The genus Verbascum Linnaeus (1753: 177) (Scrophulariaceae) includes about 360 species (Mabberley 2008). In Turkey, the genus is represented by 246 species, 130 hybrids and 6 imperfectly known or doubtful records (Huber-Morath 1978, Davis et al. 1988, Karavelioğulları 2012, 2014a, 2014b).